Deep Eutectic Solvents (DESs)-Ultrasonic-Assisted Extraction of Paeoniflorin and Paeonol from Moutan Cortex - Zhuo Chen; Jinnan Zhang; Fuwei Yang (Journal of Chemistry)
Deep eutectic solvents (DESs-)-ultrasonic-assisted extraction technology was used to evaluate and optimize the extraction process of paeoniflorin and paeonol in Moutan Cortex. First of all, 10 kinds of choline chloride-based DESs were selected as potential extraction solvents, and the DES extraction effect of choline chloride: lactic acid was determined to be the best. Then, single-factor experiments were conducted to explore the effects of DES composition (molar ratio, water content, and ratio of material to liquid) and ultrasonic treatment (ultrasonic power, extraction time, extraction temperature, and vortex time) on the yield of paeoniflorin and paeonol in Moutan Cortex. On this basis, the response surface method was used to optimize the process of ultrasonic-assisted extraction of paeoniflorin and paeonol from Moutan Cortex with DESs. The results showed that the optimum process parameters of DESs-ultrasonic-assisted extraction of paeoniflorin and paeonol from Moutan Cortex were as follows: molar ratio of choline chloride to lactic acid was 1 : 2, water content was 30%, ratio of material to liquid was 1 : 30 (g/mL), ultrasonic power was 300 W, extraction time was 33 min, extraction temperature was 50°C, and vortex time was 5 min. Under these conditions, the yield sum of paeoniflorin and paeonol in the obtained Moutan Cortex was 9.279 mg/g. The difference between the experimental value and the theoretical value was 0.333 mg/g. The results showed that the response surface method can simulate and predict the yield of paeoniflorin and paeonol in Moutan Cortex under different extraction conditions, and it was feasible to optimize the process parameters. The results of this study show that DES has great potential to replace traditional solvents in the extraction of active components of the Moutan Cortex. The study on the extraction of active components of traditional Chinese medicine by DES is helpful to expand the scope of the application of DES in traditional Chinese medicine.